1970
DOI: 10.1295/polymj.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Dual Site Character of AlEt3-ZnCl2-CCl4 Catalyst in the Copolymerization of Ethylene with Vinyl Acetate

Abstract: ABSTRACT:Copolymerization of ethylene with vinyl acetate was carried out at room temperature by the ternary catalyst system consisting of equimolar amounts of AlEts, ZnCh and CCk By solvent fractionation and thin layer chromatography analysis, the copolymerization product was found to consist of two different copolymer fractions. One was the 1 : 1 alternating copolymer and the other was identified with the copolymer produced by the usual free radical initiator under the same reaction conditions. Two different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1972
1972
1993
1993

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Especially interesting is the bimetallic complex system AlEt3 -ZnCl2 which is the basis for alternating complex copolymerization 1870,1874,2453). ESR studies have been reported for the following aluminium alkyls: AlRC1 2 125 1), AlEt 2 Cl, AlEtCI 2 , AlEt32261), AlEt3-ZnCI22453), and AlEt2Cl-ZnCI2752, 788) for initiating polymerization and copolymerization.…”
Section: Cationic Polymerization Initiated With Lewis Acidsmentioning
confidence: 99%
“…Especially interesting is the bimetallic complex system AlEt3 -ZnCl2 which is the basis for alternating complex copolymerization 1870,1874,2453). ESR studies have been reported for the following aluminium alkyls: AlRC1 2 125 1), AlEt 2 Cl, AlEtCI 2 , AlEt32261), AlEt3-ZnCI22453), and AlEt2Cl-ZnCI2752, 788) for initiating polymerization and copolymerization.…”
Section: Cationic Polymerization Initiated With Lewis Acidsmentioning
confidence: 99%
“…The gross copolymerization product obtained by the pre-mixed catalyst system Q) has already been shown to consist of the ethylenerich random copolymer corresponding to spot A, and the 1 : I-alternating copolymer corresponding to spot B. 3 The parallel behavior of the two sets of spots strongly suggests that the copolymerization product obtained by the in-situ catalyst system likewise consists of random and 1 : 1-alternaung copolymers. The gross copolymers prepared by the in-situ catalyst system were then subjected to quantitative TLC analysis to determine the compositions of fractions A and B.…”
Section: Molecular Weightmentioning
confidence: 98%
“…The TLC analysis of the copolymerization product was performed by a procedure similar to that proposed by Inagaki, et al,4 and employed in our preceding paper. 3 A commerical silica gel (GF254, Merck AG, Darmstadt) was used as the stationary phase. The gel layer was activated at l 10°C for 1 hr immediately before use.…”
Section: Thin-layer Choromatography (Tlc) Of Product Copolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…An improvement of the compatibility of the components in PP composites is achieved by using modifiers based on modified polyaminotriazoles [3,41 and copolymers of ethylene with acrylate and methacrylate comonomers containing nitrogen [5]. The effective use and estimation of the efficiency of modifiers in physical modification of PP fibres require the evaluation of i h e technological compatibility in the process of spinning [6, 71. A low compatibility with respect to polypropylene manifests itself by reduced processability and partial separation of the modifying component, which results in clogging of the spinning nozzle and breaking of the fibres.…”
Section: Introductionmentioning
confidence: 99%